2021
DOI: 10.3389/fcell.2021.790138
|View full text |Cite
|
Sign up to set email alerts
|

Stress as a Chromatin Landscape Architect

Abstract: The exponential development of methods investigating different levels of spatial genome organization leads to the appreciation of the chromatin landscape's contribution to gene regulation and cell fate. Multiple levels of 3D chromatin organization include chromatin loops and topologically associated domains, followed by euchromatin and heterochromatin compartments, chromatin domains associated with nuclear bodies, and culminate with the chromosome territories. 3D chromatin architecture is exposed to multiple f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…Inflammation-induced changes at the different levels of chromatin organization are an under-investigated area of research yet are likely to be instrumental in determining the mechanisms of long-term cellular dysfunction and the cell fate switching, such as EndMT 34 . Here, we focused on human vascular endothelial cells as a well-established model of inflammation-induced cellular dysfunction to investigate the effects of inflammatory stresses on chromatin accessibility and nucleoli-centromere dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inflammation-induced changes at the different levels of chromatin organization are an under-investigated area of research yet are likely to be instrumental in determining the mechanisms of long-term cellular dysfunction and the cell fate switching, such as EndMT 34 . Here, we focused on human vascular endothelial cells as a well-established model of inflammation-induced cellular dysfunction to investigate the effects of inflammatory stresses on chromatin accessibility and nucleoli-centromere dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Current knowledge regarding the chromatin changes in response to pro-inflammatory cytokines remains limited 34 . One study revealed an intriguing phenomenon of a cell-type-specific prolonged inflammatory response that was accompanied by increased chromatin accessibility 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In plants, such long-range interactions between promoters and distal regulatory sequences are most prominent in species with large genomes, such as maize ( Zea mays ) 23 , 24 . Modulating these interactions in response to stress is likely functionally relevant, as has been shown in Drosophila 25 and human cells 26 , but remains largely unexplored in plants.…”
Section: Introductionmentioning
confidence: 99%